Analysis Of The Welfare Level of Farmer Households Oil Palm Farmers In Pemayung Sub-District Batanghari District - Novita, Sri; Damayanti, Yusma; Sri Nurchaini, Dewi (JALOW | Journal of Agribusiness and Local Wisdom, 2024)
The level of welfare can be measured by the amount of consumption for household expenditure. This study aims to: 1) determine the level of income and household expenditure of smallholder oil palm farmers, 2) analyze the level of household welfare of smallholder oil palm farmers. The research was conducted in Pemayung District, Batanghari Regency, Jambi Province. The overall research time was conducted for one calendar month. The research objects include: income, household expenditure and welfare level. The research variables consisted of 1) household income sourced from oil palm farm income, non-oil palm farm income and outside farming, 2) welfare level of BPS 2022 indicators (population, health and nutrition, education, employment, consumption levels and patterns, housing and environment, poverty and other social). Respondents were taken purposively in each village with a total of 41 households. Data were analyzed by classifying welfare levels based on eight indicators. The results showed that 1) The average income of respondent households in the study area averaged Rp.3,281,951/month while household non-food expenditure amounted to Rp1,402,003/month and average food expenditure amounted to Rp1,231,250/month, 2) The average welfare level of oil palm farmers in Pemayung Subdistrict is in the category of moderate welfare level, namely as many as 16 farmers or 39.02%. Keywords: oil palm farmer, households, welfare level, Statistics Indonesia indicators